Efforts to Improve Understanding of the Meaning of Prayer through a Direct Practice Approach to Grade III Students of SD 008 Rambah Hilir - Kasmawati, Kasmawati; Fitri, Umi; L, Mesis (STKIP Rokania Pasir Pangaraian, 2024)
This research aims to improve the understanding of the meaning of prayer through a hands-on approach in grade III elementary school students. The method used in this study is Classroom Action Research, which is carried out in two cycles. The study subjects were 21 students in grade III of elementary school. The instruments used include observation sheets, interviews, and comprehension tests. The study results show that applying the hands-on approach can increase students' understanding of the meaning of prayer. In cycle I, students' comprehension increased by 20%, while in cycle II, it increased by 35%. These results show that the hands-on approach is effective in helping students understand the meaning of prayer more deeply.